A Step Towards Lowering Maternal Mortality: Adoption of Elements of WHO’s Safe Childbirth Checklist at A Tertiary Care Hospital of Rawalpindi, Pakistan: A Cross Sectional Survey - Saira Maroof; Zubaida Rashid; Imtenan Sharif; Marukh Alam; Rida Nawaz; Salman Nawaz; Maaz Amin; Naseer ul Islam; Syed Irshad Hussain; Aimal Khan (The International Journal of Frontier Sciences, 2019)
Abstract